Factors Affecting Work Fatigue in Nurses at the Padangsidimpuan Regional General Hospital Emergency Room in 2022 - Hanita Rosmalina; Gerry Silaban; Isyatun Mardhiyah Syahri (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Fatigue is a mechanism to protect the body from further damage resulting in recovery after rest. Fatigue generally shows different conditions for each person, but you lose efficiency and work capacity and decrease body endurance. This study aimed to determine the factors influencing work fatigue in nurses in the Emergency Room at the Padangsidimpuan City Regional General Hospital. This research is a quantitative study with a cross-sectional design. This research was conducted at the Padangsidimpuan Regional General Hospital Emergency Room. This research was conducted from July 2022 to March 2023. The population of this study was all nurses in the Emergency Room at the Padangsidimpuan Regional General Hospital, consisting of 36 nurses. The sampling technique is the total sampling technique. The research sample is 36 nurses. Data analysis in this study used the Spearman Correlation test and the Multiple Linear Regression test. The results of the study are that workload affects work fatigue p-value = 0.0014 (<0.05) r = 0.569, there is an effect of sleep quality on work fatigue p-value = 0.003 (<0.05) r = 0.656, and workload Work affects sleep quality p-value=0.002 (<0.05) r=0.256 in the Emergency Room at the Padangsidimpuan City Regional General Hospital in 2022. It is suggested that the Padangsidimpuan City General Hospital to optimize the distribution system for nurses to make the professional nurses more effective in providing health services in the Emergency Room. The need to make a policy that provides training and career development for nurses based on the competence and performance of nurses to motivate them to work even with a high workload. Moreover, involve nurses in regular training or seminars to improve their abilities and competencies in carrying out their nursing duties. Keywords: Emergency Room, Sleep Quality, Workload, Work Fatigue